Diuron status in Port Klang and screening of indigenous bacteria for potential Diuron biodegradation agent - Hanapiah, Munirah (2018)
Being as one of the main shipping ports in Malaysia, Port Klang is strategically located at the gateway of Malacca Straits and receiving water influx from two major rivers (Langat River and Klang River) and a few small tributaries. Port Klang is the busiest trading ports in Malaysia in terms of sea vessels harboured, container handled and total cargo tonnage handled. With intense shipping activities and water influx from agriculture areas, the coastal water of Port Klang is predicted to receive various organic pollutants (including Diuron) leached out from the coating paint of the moving vessels and also sources from agriculture runoff, industries, and the residential areas nearby. Diuron is one of the alternative biocides used to replace organotin compound in the formulation of antifouling paints, while also actively use as herbicide at cultivated and non-cultivated areas. Considering the physical and chemical properties of Diuron, it is lethal to targeted and non-targeted marine organisms. Thus, present study aimed [1] to assess the current concentration of Diuron from surface sediments, pore water and surface seawater samples, [2] to isolate, characterize and identify potential Diuron-degrader bacteria from sediment samples, and [3] to observe the growth performance of selected isolates exposed to the Diuron-treated media. For the assessment of Diuron, three types of samples were collected from Station 1 to Station 6 that are represent port and non-port area of Port Klang area. Bacteria strains were isolated from the collected sediment samples based on standard isolation protocols. Meanwhile, growth performance of selected isolates were observed for 7 days at 24 hours interval times. Results showed that present Diuron concentration in Port Klang was higher compared to previous Malaysian coastal water studies in both sediment (19.27 μg/kg) and surface seawater (0.53 μg/L) samples and new data recorded of Diuron was traced in pore water samples (12.91 μg/L). These contaminant level are expecting to be increase in next coming years due to growing of vessels and vigorous activities from nearby of Port Klang area. For isolation part, from all 21 isolates screened out, bacteria labelled SZZ 10 and SZZ 19 showed the capability to survive in the maximum permissible limit concentration, 430 ng/L and happened to be an excellent strains which survived up to 1000 μg/L of Diuron. These bacteria were then genetically identified as Comamonas jiangduensis (SZZ 10) and Bacillus aerius (SZZ 19) and deposited in GenBank with accession numbers KU942479, KU942480, respectively. In growth performance observation, Bacillus aerius (SZZ 19) showed the potential as biodegrader of Diuron due to its high resistance and adaptation mechanism toward toxicity of Diuron. In conclusion, Diuron was found to be pollute in the area of Port Klang with increment in concentration due to the various activities surround the Port Klang area. For a simple yet low cost bioremediation approach, an isolation of bacterial species from contaminated area was succeed in reveal the potential of Bacillus aerius as a future Diuron-degrader bacteria after several screening procedure was done. It is suggested that future works should include biodegradation of Diuron by strictly controls the crucial parameters in enhancing the bioremediation process in the effort of decontamination of Diuron from the environment soon.